1994
DOI: 10.1007/bf00121698
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of some magnesium-containing calcium phosphate cements

Abstract: Attempts were made to prepare magnesium-containing calcium phosphate cements. These were successful at the composition CaMg2(PO4)2xH20. X-ray diffraction showed that such a compound is not formed but that the cement consists of magnesium phosphate precipitated on the calcium phosphate admixture. The pH of this formulation is around 10 during setting and after. The cement is injectable. Its setting time is about 10 min. In this study compressive strength values were as high as 11 MPa and the diametral tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Due to their better biological properties compared to pure CPCs, CPCs with Mg substitution (CMPCs) are increasingly being researched [ 27 , 28 , 29 , 35 , 48 ] and have proven in various studies to be, in the form of cement pastes, very promising in terms of biocompatibility, osseointegration, successive degradation and absorption [ 27 , 28 , 32 , 48 ]. For the treatment of many defects, however, the use of precisely fitting and dimensionally stable bone substitutes of defined shape is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their better biological properties compared to pure CPCs, CPCs with Mg substitution (CMPCs) are increasingly being researched [ 27 , 28 , 29 , 35 , 48 ] and have proven in various studies to be, in the form of cement pastes, very promising in terms of biocompatibility, osseointegration, successive degradation and absorption [ 27 , 28 , 32 , 48 ]. For the treatment of many defects, however, the use of precisely fitting and dimensionally stable bone substitutes of defined shape is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of CMPCs in bone healing has been described in the literature and it has been shown that pastes and pre-hardened cylinders of CMPCs are biocompatible, well-integrated into the surrounding bone and rapidly replaced by newly formed trabecular bone [ 27 , 31 , 32 ]. However, the use of self-setting cement pastes is limited, e.g., because they are applied into the defect in a viscous condition, have to harden for several minutes at the implant site [ 33 , 34 , 35 ] and are difficult to shape in some clinical situations [ 36 ]. Biocements, which can be produced using three-dimensional (3D) powder printing to form inherently stable, three-dimensional solids of defined shape, offer a more diverse range of possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…As an important biomedical material with outstanding bioactivity, biocompatibility, plasticity and injectability, calcium phosphate bone cement (CPC) could be adapted to repair bone defects with a complex anatomical shape [1], avoiding the deficiencies of block-like/granular calcium phosphate ceramics. Since its emergence in the mid-1980s [2,3], CPC has already achieved great progress, and a variety of excellent bone cement systems like tetracalcium phosphate (TTCP)or tricalcium phosphate (TCP)-based CPC and strontium (Sr)-or magnesium (Mg)-doped CPC [4][5][6][7] have been developed. With a major hydration product, hydroxyapatite (HAP), which is similar to inorganic constituents of human bone, CPC has been widely used as an indispensable injectable material in the orthopedic clinical setting due to its excellent bioactivity, suitable setting time and high compressive strength [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Uma das possíveis substituições é a de composição CaMg 2 (PO 4 ) 2 .H 2 O, onde dois íons de magnésio substituem dois íons de cálcio. O que de fato acontece, após análises do cimento (Ginebra, et al, 1994), é a formação de fosfatos de magnésio precipitados numa mistura com fosfatos de cálcio. E apesar do cimento obedecer a vários dos pré-requisitos para sua aplicação, seu pH pode chegar a valores tão altos quanto 10 durante a reação de pega e mesmo permanecer neste valor após algum tempo.…”
Section: Fosfatos De Cálcio Substituídosunclassified